Fundamental Toxicology - Duffus, John H; Ed (Royal Society of Chemistry, 2006)
Fundamental Toxicology is a comprehensive review of toxicology. It is based on the highly successful 'Fundamental Toxicology for Chemists' and has been enriched and expanded.